Evaluation of Single-Bundle versus Double-Bundle PCL Reconstructions with More Than 10-Year Follow-Up - Masataka Deie; Nobuo Adachi; Atsuo Nakamae; Kobun Takazawa; Mitsuo Ochi (The Scientific World Journal)
Background. Posterior cruciate ligament (PCL) injuries are not rare in acute knee injuries, and several recent anatomical studies of the PCL and reconstructive surgical techniques have generated improved patient results. Now, we have evaluated PCL reconstructions performed by either the single-bundle or double-bundle technique in a patient group followed up retrospectively for more than 10 years. Methods. PCL reconstructions were conducted using the single-bundle (27 cases) or double-bundle (13 cases) method from 1999 to 2002. The mean age at surgery was 34 years in the single-bundle group and 32 years in the double-bundle group. The mean follow-up period was 12.5 years. Patients were evaluated by Lysholm scoring, the gravity sag view, and knee arthrometry. Results. The Lysholm score after surgery was 89.1±5.6 points for the single-bundle group and 91.9±4.5 points for the double-bundle group. There was no significant difference between the methods in the side-to-side differences by gravity sag view or knee arthrometer evaluation, although several cases in both groups showed a side-to-side difference exceeding 5 mm by the latter evaluation method. Conclusions. We found no significant difference between single- and double-bundle PCL reconstructions during more than 10 years of follow-up.